Talking about child abuse under The Child Act 2001 / Tengku Adida Tengku Zainal Mulok - Tengku Zainal Mulok, Tengku Adida (University Publication Centre (UPENA), 2006)
The world was stunned when it received a tragic and shocking news concerning maltreatment of child. Child abuse and neglection are prevalent forms of child maltreatment and these issues are worsening. This problem has been rooted and encompassed in one's life. Physical, emotional or sexual abuse normally occur when the abuser feels he is stronger, more energetic and powerful in terms of mental and psychological aspects compared to the child's. Not surprisingly, children are often the victims of abuse. In fact even in Malaysia there are worryingly rising cases pertaining this matter. Since the issue of child abuse is a social problem and not a personal one, it occurs everywhere in the world and furthermore it has been heated discussed and debated through the electronic and printed media. Therefore the writer wishes to discuss this matter in respect of Child Act 2001 with three goals, firstly; by explaining the scenario of child abuse as well as the protections provided under the Act, secondly; to expose or to increase the public awareness and understanding as regards to this issue and thirdly; to give some recommendations and suggestions in improving services and safeguarding the interests and welfare of innocent children.